2015
DOI: 10.1016/j.surg.2015.01.027
|View full text |Cite
|
Sign up to set email alerts
|

The impact of resident involvement on surgical outcomes among patients undergoing hepatic and pancreatic resections

Abstract: Background Resident participation during hepatic and pancreatic resections varies. The impact of resident participation on surgical outcomes in hepatic and pancreatic operations is poorly defined. Methods We identified 25,511 patients undergoing a hepatic or pancreatic resection between 2006 and 2012 using the American College of Surgeons National Surgical Quality Improvement Program database. Multivariate regression models were constructed to determine any association between resident participation and surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 17 publications
2
19
0
1
Order By: Relevance
“…24 Despite improvements in mortality, the morbidity associated with hepatic resection remains in the range of 30-40%. 24,25 In particular, the morbidity and mortality following liver resection combined with vascular resection can be considerably higher than a routine hepatectomy. For example, de Jong et al recently reported on the impact of PV resection on perioperative outcomes in 305 patients who underwent resection for hilar cholangiocarcinoma.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…24 Despite improvements in mortality, the morbidity associated with hepatic resection remains in the range of 30-40%. 24,25 In particular, the morbidity and mortality following liver resection combined with vascular resection can be considerably higher than a routine hepatectomy. For example, de Jong et al recently reported on the impact of PV resection on perioperative outcomes in 305 patients who underwent resection for hilar cholangiocarcinoma.…”
Section: Discussionmentioning
confidence: 57%
“…Perioperative and technical advances have dramatically reduced the risks associated with hepatic resection such that most centers report a mortality of less than 2‐3% for liver surgery . Despite improvements in mortality, the morbidity associated with hepatic resection remains in the range of 30‐40% . In particular, the morbidity and mortality following liver resection combined with vascular resection can be considerably higher than a routine hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, the resident's role was that of a first assistant [5]. Studies that investigate the topic of education by analyzing the NSQIP database usually give no further information about the role of the resident [12].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, recent evidence has shown that resident participation as operating surgeons in surgical procedures of varying complexity, may be considered ethical, safe, and responsible whenever implemented in the framework of a residencytraining program with continuous supervision and national accreditation [7]. Moreover, recent results from the ACS NSQIP database found that although both liver and pancreas resections with resident participants resulted in a longer operative time, other parameters such as duration of stay and perioperative major morbidity were unaffected [17]. Sachs et al [18] characterized and quantified the procedural volumes of complex HPB procedures among graduating chief residents, concluding that half performed fewer than 10 cases in each of the liver, pancreas, or biliary categories.…”
Section: Surgical Skills Learning Curvementioning
confidence: 99%